Question

( operatorname{son}(7) quadleft(x^{2}-1right)+(x-1)^{2}+sqrt{x^{2}-3 x+2}=0 )
Apply elimination metwo o
a) ( quad ) if ( x=1 ) ( 0+0+sqrt{1-3+2}=0 )
hence satisfly ( left(x^{2}right) )
( (b) )
( x=4 quad|16-1|+(3)^{2}+sqrt{16-12+2}= )
( Rightarrow 15+9+sqrt{6} eq 0 )
Not solu
2
( x=-2 )
( therefore quad|3|+(-5)^{2}+sqrt{4+6+2} eq )
thus Not do 14 ( therefore sqrt{A v}=x^{2} 1 )

# 7. (0) 9 +27 If X-1 +(x-1) + Vx? --3x + 2 = 0, then value of x is : (B)4 (C)-2 (A) 1 (D) None of these

Solution